2008
DOI: 10.1097/01.jnr.0000387313.20386.0a
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Appropriate Chinese Terms to Represent Intensity and Types of Physical Activity Terms for Use in the Taiwan Version of IPAQ

Abstract: In order to analyze the health risks of insufficient activity by international comparisons, the first author obtained the permission to translate and develop a Taiwan version of the International Physical Activity Questionnaire (IPAQ). The objective was to determine culturally sensitive Chinese translations for the terms "moderate", "vigorous" and "physical activity" as well as to identify representative types of physical activity for Taiwanese. This study used discussions by 12 expert focus groups, 6 expert a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 12 publications
0
157
0
Order By: Relevance
“…It comprises 30 questions to assess the following seven aspects: (1) physical activity; (2) sleep; (3) sedentary behavior; (4) dietary habit; (5) confidence; (6) knowledge; and (7) perceived body shape. In Liou’s studies [17,18] demonstrated that this scale had well content validity index (CVI) and acceptable test/retest reliability. With consent from the author, a portion of the questionnaire contents were extracted for use: physical activity levels; sedentary behaviors (time spent watching television, playing video games, or using the computer); dietary habits; and perceived body shape.…”
Section: Methodsmentioning
confidence: 99%
“…It comprises 30 questions to assess the following seven aspects: (1) physical activity; (2) sleep; (3) sedentary behavior; (4) dietary habit; (5) confidence; (6) knowledge; and (7) perceived body shape. In Liou’s studies [17,18] demonstrated that this scale had well content validity index (CVI) and acceptable test/retest reliability. With consent from the author, a portion of the questionnaire contents were extracted for use: physical activity levels; sedentary behaviors (time spent watching television, playing video games, or using the computer); dietary habits; and perceived body shape.…”
Section: Methodsmentioning
confidence: 99%
“…The non-athlete group matched the athlete group in age and education, but they had no experience of playing table tennis, nor any experience of athlete training. The non-athlete group had a moderate physical activity level which was measured by the Taiwan version of the International Physical Activity Questionnaire (IPAQ) (Liou et al, 2008). All the participants were right-handed and had normal or corrected to normal visual acuity.…”
Section: Methodsmentioning
confidence: 99%
“…“Exhaustion” was indicated if the participants responded with “a moderate amount of the time” or “most of the time” to either of the following two statements: “I felt everything I did was an effort” or “I could not get going.” The statements were obtained from the Center for Epidemiological Studies-Depression Scale. [24] “Low physical activity” was defined by sex-specific, low weekly energy expenditure measured using the Taiwan International Physical Activity Questionnaire-Short Form [25] instead of the Minnesota Leisure Time Physical Activity Questionnaire. [26] “Slow walking speed” based on the time to walk for 5 m was below certain sex- and height-specific cut-points.…”
Section: Methodsmentioning
confidence: 99%